Urgensi Adanya Aturan Khusus Terkait Hukum Transportasi Online Pada PT. Gojek - Dameria, Fiorella Angella; Lie, Gunardi; Syailendra, Moody R. (Wajah Hukum, 2023)
Indonesia is home to 300 million people and has one of the most densely populated cities in the world. Unfortunately, Indonesia is still listed as a developing country. Responding to the absence of a quality public transport system, the private and informal sector for transportation has developed a solution. They fill the gaps in Indonesia's inadequate transportation system by providing effective means of transportation for people amidst an economic downturn. This research is normative juridical research. The purpose of this study is to find out the juridical rules governing PT. GOJEK as a legal entity and the legal urgency of online transportation for PT. GOJEK to have its own rules. The government should be able to immediately issue special rules for PT. GOJEK in the interest of the State, PT GOJEK, Drivers and Drivers.